Impregnated activated carbon for the adsorption of Gd(III) radionuclides from aqueous solutions. (4th July 2018) - Rashad, Ghada M.; Mahmoud, Mamdoh R.; Sheha, Reda R.
ABSTRACT: Activated carbons (ACs) impregnated by FeCl3, SnCl4 and ZnCl2 are used as adsorbents for the removal of Gd(III) radionuclides from aqueous solutions. Adsorption of Gd(III) is investigated as a function of pH, concentration of adsorbate, contact time, ionic strength and temperature. Gadolinium is efficiently removed (R% > 95%) at pH values ≥4.8 (for FeAC and SnAC) and 2.9 (for ZnAC). The pseudo-first-order, the pseudo-second-order and Elovich kinetic models are used to analyze the kinetic data of Gd(III), at the studied concentrations (30, 100 and 200 mg/L) onto the employed materials. Of these models, Elovich is the only one that well-fitted the experimental kinetics onto the applied materials at all of the studied Gd(III) concentrations. Equilibrium data of Gd(III) are analyzed by the Freundlich, Temkin, Dubnin–Radushkevich (D-R) and Redlich–Petrson isotherm models. The adsorption efficiency of Gd(III) onto FeAC and SnAC is deleteriously affected by increasing the ionic strength, while adsorption onto ZnAC is unaffected. The thermodynamic parameters are calculated and it is revealed that the adsorption of Gd(III) onto the employed materials is an endothermic process. Desorption studies of Gd(III)-loaded ACs are performed using different desorbing agents (HCl, ZnCl2, FeCl3 and SnCl4 ) at various concentrations (0.0005, 0.0025, 0.01 and 0.025 M).